2007
DOI: 10.1016/j.juro.2007.03.110
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptors in the Developing Genital Tubercle: Implications for the Endocrine Disruptor Hypothesis as the Etiology of Hypospadias

Abstract: Progesterone receptors are expressed in developing genital tubercles, suggesting a direct role of progesterone in normal genital tubercle patterning. Their increasing expression until birth also implies increasing sensitivity of the genital tubercles to the effects of estrogenic and progestogenic endocrine disruptors during fetal life. Ethinyl estradiol and testosterone propionate lead to opposing effects on progesterone receptor expression, in addition to their opposing morphological effects on the genital tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
2
11
0
3
Order By: Relevance
“…Increasing expression of progesterone receptors until birth also implies increasing sensitivity of the genital tubercles to the effects of estrogenic and progestogenic endocrine disruptors during fetal life. Ethinyl estradiol and testosterone propionate lead to opposing effects on progesterone receptor expression, in addition to their opposing morphological effects on the genital tubercles [10]. Our data demonstrate the decreased microvessel density in prepuces of hypospadiac patients for the first time.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Increasing expression of progesterone receptors until birth also implies increasing sensitivity of the genital tubercles to the effects of estrogenic and progestogenic endocrine disruptors during fetal life. Ethinyl estradiol and testosterone propionate lead to opposing effects on progesterone receptor expression, in addition to their opposing morphological effects on the genital tubercles [10]. Our data demonstrate the decreased microvessel density in prepuces of hypospadiac patients for the first time.…”
Section: Discussionmentioning
confidence: 61%
“…They speculated that this might be the postnatal result of disrupted estrogen and androgen receptor interactions during the intrauterine development of the external genitalia. Finally, Agras et al [10] reported that progesterone receptors are expressed in developing genital tubercles, suggesting a direct role of progesterone in normal genital tubercle patterning. Increasing expression of progesterone receptors until birth also implies increasing sensitivity of the genital tubercles to the effects of estrogenic and progestogenic endocrine disruptors during fetal life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the incidence of hypospadias has been shown to be increased in families undergoing in vitro fertilization (Nordenvall et al, 2013), perhaps because progesterone is administered to maintain receptivity of uterus to the embryo. Progestins have been implicated as a potential cause of hypospadias in both animal and human studies (Carmichael et al, 2005; Willingham et al, 2006a; Agras et al, 2007). Animal models of hypospadias have demonstrated a causal relationship between hypospadias and prenatal exposure to a variety of agents: estrogens, progesterone, Loratidine, “androgen blockers” (flutamide, finasteride, anti-androgenic fungicides [vinclozolin and procymidone], and phthalates) (Clark et al, 1993; Ostby et al, 1999; Kojima et al, 2002; Kim et al, 2004; Carmichael et al, 2005; Foster and Harris, 2005; Buckley et al, 2006; Willingham et al, 2006b; Ormond et al, 2009; Rider et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-specificity of estrogen function is conferred by expression of estrogen receptors α and β. Interestingly, a potent estrogen, estradiol, was found to play several important functions in sexual differentiation of the male, in particular, at maturation of the sperm [13] and development of the prostate [9] and phallus [14]. Furthermore, developing male phallus also contains receptors for another female hormone, progesterone which role is not yet clears [15].…”
Section: Editorialmentioning
confidence: 99%